A Fiber-Optic Fabry-Perot Accelerometer Based on High-Speed White Light Interferometry Demodulation - Zhao, Zhihao; Yu, Zhihao; Chen, Ke; Yu, Qingxu (Journal of lightwave technology, 2018)
A fiber-optic Fabry-Perot (F-P) accelerometer with high resolution, high dynamic range, high speed, and absolute measurement capability was developed and demonstrated in elevator health monitoring. The sensor element is based on a mesh diaphragm mass-loaded compact structure, and the F-P cavity interrogation was achieved by utilizing a high-speed white light interferometry demodulation algorithm. The displacement of inertial mass representing the change of F-P cavity was measured and translated to acceleration in real time. The results indicate a resonance frequency of 270 Hz and axial sensitivity of 3.86 μm/g within the frequency bandwidth of 10-120 Hz for the sensor. In experimental tests, the acceleration resolution achieved 8.5 μg within a ± 30 g maximum measurement range. The performance of the sensing system was compared with a commercialized piezoelectric accelerometer in monitoring the acceleration of an elevator.